Requirements Engineering for Digital Health - Fricker, Samuel A (Springer, 2015)
Abstract Healthcare is the biggest and fastest growing industry in the world and is one of the domains that are expected to grow significantly over decades to come. Underlying cause for this are the current demographic developments which are showing similar patterns almost worldwide with a strong growth of the population share of individuals over 65 years of age...